Homeostasis Imbalance of YY2 and YY1 Promotes Tumor Growth by Manipulating Ferroptosis. Issue 13 (4th March 2022) - Li, Yanjun; Li, Juan; Li, Zhuolin; Wei, Mankun; Zhao, Hezhao; Miyagishi, Makoto; Wu, Shourong; Kasim, Vivi
Abstract: Ferroptosis is a type of programmed cell death caused by disruption of redox homeostasis and is closely linked to amino acid metabolism. Yin Yang 2 (YY2) and its homolog Yin Yang 1 (YY1) are highly homologous, especially in their zinc‐finger domains. Furthermore, they share a consensus DNA binding motif. Increasing evidences have demonstrated the tumor suppressive effect of YY2, in contrast with the oncogenic YY1; however, little is known about the biological and pathological functions of YY2. Here, it is determined that YY2 induces tumor cell ferroptosis and subsequently suppresses tumorigenesis by inhibiting solute carrier family 7 member 11 (SLC7A11) transcription, leading to the decreased glutathione biosynthesis. Furthermore, YY2 and YY1 bind competitively to the same DNA binding site in the SLC7A11 promoter and antagonistically regulate tumor cell ferroptosis, thus suggesting the molecular mechanism underlying their opposite regulation on tumorigenesis. Moreover, mutations of YY2 zinc‐finger domains in clinical cancer patients abrogate YY2/SLC7A11 axis and tumor cell ferroptosis. Together, these results provide a new insight regarding the regulatory mechanism of ferroptosis, and a mechanistic explanation regarding the tumor suppressive effect of YY2. Finally, these findings demonstrate that homeostasis between YY1 and YY2 is crucial for maintaining redox homeostasis in tumor cells. Abstract : Yin Yang 2 (YY2) is highly homologous with Yin Yang 1 (YY1), a famous oncogene; however, little is known about its functions. YY2 competes with YY1 to bind to SLC7A11 promoter and regulates it antagonistically, resulting in the opposite regulation on glutathione synthesis, ferroptosis, and tumor progression, indicating that YY2/YY1 homeostasis is crucial for maintaining redox homeostasis in tumors.